'Devote the best years of their lives': British Solutions to Natal's Defence Concerns in Nineteenth-Century Southern Africa. Issue 1 (March 2019) - Ivey, Jacob
Abstract : The annexation and establishment of Natal as a British colony by 1845 was an event defined by conflict and concerns for security in British Southern Africa. The threat of invasion from the nearby Zulu kingdom or the possibility of an indigenous uprising continued to cast a shadow over the growth and expansion of the colony during the following decades. In response, those living within the colony offered multiple solutions, both actual and theoretical, related to the protection and stability of this emerging colonial state, including white volunteer corps, mounted police, and even indigenous levies. This paper examines the debate that defined these proposed solutions from 1845 to the Anglo–Zulu War of 1879. Whether from within the colony itself or from other regions of the British Empire, the suggested solutions and the debate over security were illustrative of the concern about external and internal threats that permeated the European public consciousness of British Natal. Some residents of the colony offered their own military expertise (or lack thereof); others looked to the Afrikaner population as a model for control; and a small number, who did not even reside in the colony, expressed their readiness to 'devote the best years of their lives' to the security of the colony. Such willingness, along with the other solutions to the issue of colonial security in British Natal, sheds considerable light on the emergence of imperial power in nineteenth-century Southern Africa, and constitutes a valuable addition to the history of Natal, settler colonies more generally and the British Empire at large.